STUDI TENTANG TOKOH LURAH TUTUAN DALAM BABAD PASEK - I Putu Adi Saputra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
This study talks about Babad Pasek, one of the chronicles in the Balinese history literature. The focus of this research is the figure of Lurah Tutuan. Using the literary approach, the Tutuan Lurah figure is studied from the physical aspects, psiology aspects, and sociology. The results showed that Lurah Tutuan, the son of Mpu Raragunting, inherited his father's religious symbol, so he was highly respected by his people and was made a ruler. However, because he was young and he couldn’t control his love for Ni Gunaraksa, Lurah Tutuan was willing to break the tradition of his Clan. Analysis of the figures in Babad literature is important for the readers, to avoid in a narrow interpretation or understanding